IEO Annual Report 2010. (Independent Evaluation Office Reports; Independent Evaluation Office Reports, 2010)
The Independent Evaluation Office's (IEO) Annual Report 2010 highlights that in FY2010, the IEO expended approximately 95 percent of its budgetary resources. The corresponding underspending (about 5 percent of the budget) resulted from several vacancies for significant periods throughout the year. Staffing developments over the course of FY2010 highlighted the costs of high staff turnover for the IEO's work. In July 2009, the IEO undertook an assessment of recent staffing experience, the main challenges encountered in recruiting and retaining employees, and the aspects of the IEO's employment policies that contribute to these difficulties.